Barriers in accessing HIV care for Francophone African, Caribbean and Black people living with HIV in Canada: A scoping review - Djiadeu, Pascal; Yusuf, Abban; Ongolo-Zogo, Clémence; Nguemo, Joseph; Odhiambo, Apondi J.; Mukandoli, Chantal; Lightfoot, David; Mbuagbaw, Lawrence; Nelson, LaRon. E. (BMJ Open, 2020)
Introduction In 2001, 50%–55% of French-speaking minority communities did not have access to health services in French in Canada. Although Canada is officially a bilingual country, reports indicate that many healthcare services offered in French in Anglophone provinces are insufficient or substandard, leading to healthcare discrepancies among Canada’s minority Francophone communities. Objectives The primary aim of this scoping systematic review was to identify existing gaps in HIV-care delivery to Francophone minorities living with HIV in Canada. Study design Scoping systematic review. Data sources Search for studies published between 1990 and November 2019 reporting on health and healthcare in Francophone populations in Canada. Nine databases were searched, including Medline, Cumulative Index to Nursing and Allied Health Literature, the Cochrane Library, the National Health Service Economic Development Database, Global Health, PsychInfo, PubMed, Scopus and Web of Science. Study selection English or French language studies that include data on French-speaking people with HIV in an Anglophone majority Canadian province. Results The literature search resulted in 294 studies. A total of 230 studies were excluded after duplicates were removed. The full texts of 43 potentially relevant papers were retrieved for evaluation and data extraction. Forty-one studies were further excluded based on failure to meet the inclusion criteria leaving two qualitative studies that met our inclusion criteria. These two studies reported on barriers on access to specialised care by Francophone and highlighted difficulties experienced by healthcare professionals in providing quality healthcare to Francophone patients in Ontario and Manitoba. Conclusion The findings of this scoping systematic review highlight the need for more HIV research on linguistic minority communities and should inform health policymaking and HIV/AIDS community organisations in providing HIV care to Francophone immigrants and Canadians.

Gaps in knowledge and practices of malaria prevention in Francophone African immigrants in Metropolitan Edmonton - Hanna, Taylor A.; Ahmed, Ali; Vincent, Rémi; Coulibaly, Kongnon Sangué; Ahmed, Youssef; Petrick, Ryland; Vincent, Etienne; El Hafid, Mélanie; Hawkes, Michel T.; Ravi, Srilata; Gnidehou, Sedami (Malaria Journal, 2022)
Background Important knowledge gaps exist in the understanding of the management of the risks of imported malaria in Canada among Francophone immigrants from sub-Saharan Africa (FISSA). The aim of this cross-sectional study was to investigate the malaria related-knowledge, attitude and practices (KAP) of FISSA in Edmonton, where these immigrants are in an official minority language situation and the impact of language barriers on these factors. Methods A structured survey was used to examine the KAP of 382 FISSA in the Edmonton area from 2018 to 2019. Fisher’s Exact Test was applied to determine if there were associations between knowledge of malaria and different risk factors. Results Almost all FISSA (97%) had an accurate knowledge of fever as the key symptom of malaria. Interestingly, 60% of participants identified bed nets as a preventive method and only 19% of participants had accurate knowledge of malaria transmission. An accurate knowledge of symptoms was significantly associated with a high perceived risk of contracting malaria [odds ratio (OR) 4.33, 95% confidence interval (CI) 1.07–20.62]. Furthermore, even though 70% of FISSA had a high perceived risk of contracting malaria in endemic regions, only 52% of travellers had a pre-travel medical encounter. Importantly, language was not the predominant reason for not seeking pre-travel medical advice, although 84% of respondents chose French as their official language of preference when seeking medical advice. Having a French-speaking physician was correlated with satisfactory prevention knowledge (OR 1.96, 95% CI 1.16–3.35). With respect to health-seeking behaviour, 88% of respondents with a child < 5 years of age would seek medical care for fever in the child after travel to sub-Saharan Africa (SSA). Conclusion This study highlights that factors other than knowledge, risk assessment, and language might determine the lack of compliance with pre-travel medical encounters. It underscores the need for effective strategies to improve this adherence in minority settings.

Access to healthcare services and confidence in healthcare professionals’ management of malaria: the views of Francophone sub-Saharan African Immigrants living in western Canada - Vincent, Rémi; Coulibaly, Kongnon Sangué; Ahmed, Ali; Ahmed, Youssef; Hanna, Taylor A.; Ravi, Srilata; Hawkes, Michael T.; Gnidehou, Sedami (BMC Public Health, 2023)
Abstract Background There is a paucity of knowledge about the healthcare attitudes and practices of French-speaking immigrants originating from Sub-Saharan Africa (FISSA) living in minority settings. The purpose of this study was to characterize FISSA healthcare experiences and confidence in the malaria-related knowledge of health professionals in Edmonton. Methods A structured survey was used to examine a cohort of 382 FISSA (48% female; 52% male) living in Edmonton. FISSA general healthcare attitudes, experiences and satisfaction with the Canadian healthcare system were studied. Healthcare Competency Perception (HCP) was characterized by using an index score. Statistical analyses were performed to evaluate the impact of healthcare experiences and other outcomes. Results Intriguingly, while only 42% of FISSA had a French-speaking family physician, 83% (197/238) of those who had received health care services in Alberta found that access to medical treatment was easy, and 77% (188/243) were satisfied with received care. Although 70% (171/243) of FISSA did not receive services in French, 82% (199/243) surprisingly reported having good levels of comprehension during their visits. Satisfaction with care was associated with having a family physician (p = 0.018) and having health insurance (p= 0.041). Nevertheless, confidence in the healthcare system’s ability to treat malaria effectively was significantly lower, with only 39% (148/382) receiving a positive score on the HCP index. Conclusion This study provides an important insight into FISSA experience with and perception of the Alberta’s healthcare system.